Characterization of a Novel Polysaccharide-Iron(III) Complex and Its Anti-Anemia and Nonspecific Immune Regulating Activities - Zhang, Yun; Ma, Fanyi; Zhu, Jinhua; Du, Zuliang; Zhao, Ying-Yong; Liu, Xiuhua (Mini Reviews in Medicinal Chemistry, 2017)
Objective: Dioscorea opposita Thunb is the famous food and traditional medicine in China and it was rich in polysaccharides. Polysaccharides of Dioscorea Opposita Thunb possess immunoregulatory activity, free radical scavenging activity and anti-diabetic activity. A novel polysaccharide- iron(III) complex (CYPIC) was synthesized by using crude polysaccharide extracted from Dioscorea opposita Thunb. The component, structure, morphology and molecular weights of CYPIC were analysed, and the anti-anemia, acute toxicity and nonspecific immune regulating activities of CYPIC were assayed. The results showed that CYPIC could increase red blood cell count (RBC), hemoglobin (Hb), hematocrit (HCT), thymus and spleen index of mice with iron deficiency anemia (IDA). Although the structure and deeper mechanisms of CYPIC should be further studied, CYPIC has the potential to be used as an iron supplement for the treatment of iron deficiency anemia. Conclusion: The large scale industrial production was suggested due to the simple preparation processing of CYPIC.
Keywords: iron supplement